The Effect of Problem-Based Learning Management Combined with the Think-Pair-Share Technique on Promoting Problem-Solving Ability in Social Studies on Basic Economics for Matthayomsuksa 1 Students - Singthong, Sawat; Wattanaudomchai, Surachai; Witcharapote, Jiraporn (Journal of Buddhist Education and Research (JBER), 2026)
This research aimed to: 1) compare students’ problem-solving abilities before and after learning through Problem-Based Learning enhanced with the Think-Pair-Share technique, and 2) investigate students’ satisfaction with Problem-Based Learning enhanced with the Think-Pair-Share technique. This study employed a pre-experimental design using a one-group pretest-posttest design. Target Group consisted of 25 Grade 7 students from Ban Huai Rae School, Khon Kaen Primary Educational Service Area Office 2, during the first semester of the 2025 academic year. The research instruments included: 1) five lesson plans for Problem-Based Learning enhanced with the Think-Pair-Share technique, totaling 10 hours, 2) a 20-item problem-solving ability assessment, and 3) a 15-item satisfaction questionnaire. Data analysis employed mean, standard deviation, and dependent samples t-test statistics. The research findings revealed that: 1. Students’ problem-solving ability after the intervention showed a mean score of 14.92 (σ = 2.46), which was significantly higher than the pre-intervention mean score of 8.92 (σ = 2.41) at the .05 statistical significance level. 2. Students’ satisfaction with Problem-Based Learning enhanced with the Think-Pair-Share technique was at the highest level (μ = 4.66, σ = 0.34). When examined by dimension, the benefits received dimension showed the highest mean (μ = 4.68, σ = 0.30), followed by the activity organization dimension (μ = 4.66, S.D. = 0.37), and the classroom atmosphere dimension (μ = 4.64, σ = 0.36), respectively.